2013
DOI: 10.1371/journal.pone.0054628
|View full text |Cite
|
Sign up to set email alerts
|

Both Serum Apolipoprotein B and the Apolipoprotein B/Apolipoprotein A-I Ratio Are Associated with Carotid Intima-Media Thickness

Abstract: BackgroundPrevious studies indicated that apolipoprotein measurements predicted cardiovascular disease (CVD) risk; however, associations between apolipoproteins and carotid intima-media thickness (CIMT) were less explored.Methodology and Principal FindingsThe cross-sectional study included 6069 participants aged 40 years or older with NGT from Shanghai, China. Serum fasting traditional lipids (total cholesterol [TC], low-density lipoprotein cholesterol [LDL-C], high-density lipoprotein cholesterol [HDL-C] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
1
30
0
2
Order By: Relevance
“…Our finding was concordant to those of Huang et al who found that both apoB levels and apoB/apoA-I ratio were associated to increased CIMT (34). As reported by Dahlen et al we also observed that high apoB/apoA-I ratio, and not serum lipid profile, were associated with increased CIMT (35).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding was concordant to those of Huang et al who found that both apoB levels and apoB/apoA-I ratio were associated to increased CIMT (34). As reported by Dahlen et al we also observed that high apoB/apoA-I ratio, and not serum lipid profile, were associated with increased CIMT (35).…”
Section: Discussionsupporting
confidence: 92%
“…For example, levels of ApoB have been associated with the increased carotid intima-media thickness, (Huang et al 2013) and LDL/HDL is an independent predictor of vulnerable coronary plaque (Fujihara et al 2013). PAI-1, a principal inhibitor of fibrinolysis, is induced in thrombotic, fibrotic, and cardiovascular diseases, which in turn primarily afflict the older population.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that only the apo B and the apo B/apo A-I ratio remained significantly associated after the adjustment for traditional risk factors (46). Similarly, the association of the same parameters with the media-intima thickness suggest they may be early predictors of atherosclerosis (48).…”
Section: Apolipoproteinsmentioning
confidence: 95%
“…In fact, several investigators confirmed its usefulness in the prediction of cardiovascular events (46). Apo A and B are easy to be measured and showed to be useful in the prediction of cardiovascular events in some studies (45)(46)(47)(48). The meta-analysis carried out with 23 studies showed that the greatest concentrations of apo B determined a relative risk of 1.99 for events, whereas the lowest levels of apo A-I raised the risk in 62% (47).…”
Section: Apolipoproteinsmentioning
confidence: 96%